2011
DOI: 10.1002/pmic.201000580
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the effects of the immunomodulatory mycotoxin deoxynivalenol

Abstract: The mycotoxin deoxynivalenol (DON) contaminates cereals worldwide and is a common contaminant in the Western European diet. At high doses, DON induces acute gastrointestinal toxicity; chronic, low-dose effects in humans are not well described, but immunotoxicity has been reported. In this study, 2-DE was used to identify proteomic changes in human B (RPMI1788) and T (JurkatE6.1) lymphocyte cell lines after exposure to minimally toxic concentrations (up to 500 ng/mL) for 24 h. Proteins which changed their abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The metabolism results of DON-immunotoxicity were in unexpected accordance with the conclusion of proteomics [25] and genomics [26].…”
Section: Integrated Key Different Metabolic Pathwayssupporting
confidence: 72%
See 1 more Smart Citation
“…The metabolism results of DON-immunotoxicity were in unexpected accordance with the conclusion of proteomics [25] and genomics [26].…”
Section: Integrated Key Different Metabolic Pathwayssupporting
confidence: 72%
“…Collectively, these studies have revealed that the metabolic pathways of oxidative metabolism [20], glycolysis [21], and glutaminolysis [22] preferentially fuel the cell fate decisions and effector functions of immune cells [23]. can produce the impairment of glycolysis (and gluconeogenesis) and, subsequently, lead to reduced energy generation [25]. A research report [26] of gene pathway analysis M A N U S C R I P T…”
Section: Integrated Key Different Metabolic Pathwaysmentioning
confidence: 99%
“…Reduced cell viability due to DON exposure in the current series of experiments was similar to previous data and thus we selected doses and an exposure period (24 h) associated with modest (~20%) reduction in cell viability in the two cell lines representing doses at the lower end of a range used by others [23,24]. The above mentioned exposure period was also chosen based on previous studies analyzing the effects of DON on immune cell lines [16], on reproducibility and reduced variability of cell viability and a significant decrease in cell viability after a 30 h exposure period. As our objective was to induce low to moderate changes to cell viability, a 24 h exposure period was shown to be a reasonable compromise between establishing a real effect consistent with human exposure and the induction of cell death.…”
Section: Discussionmentioning
confidence: 58%
“…The development and application of "omics" techniques to develop potential mechanism-based biomarkers is a promising approach and we recently identified a number of proteins altered in expression following DON exposure in human cells lines [16]. We now extend this work to compare phosphoprotein expression in human B (RPMI1788) and T (Jurkat E6.1) lymphocyte cell lines exposed to DON at a maximum concentration of 500 ng DON/mL for a period of up to 54 h. These cell types represent major cellular components of the adaptive immune response and have been used extensively previously [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics facilitates large-scale identification and quantification of proteins, providing information on protein expression and post-translational modification (Farley and Link, 2009; Mallick and Kuster, 2010). Proteome and phosphoproteome changes occurring after prolonged (6 h or 24 h) DON treatment have been previously measured in human B and T cell lines (Osman et al , 2010; Nogueira da Costa et al , 2011a; Nogueira da Costa et al , 2011b). While these studies are important for identification of biomarkers of effect, they are not informative from perspective of early events and signaling within the macrophage, a primary target of DON which mediates innate immune activation (Zhou et al , 2003; Pestka, 2008).…”
Section: Introductionmentioning
confidence: 99%